2023
DOI: 10.3390/jcs7070278
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based White Eggshell as a Value-Added Filler in Poly(Lactic Acid) Composites

Abstract: Based on its positive environmental impact, poly(lactic acid) (PLA) has been a gradual substitute for synthetic plastics used in diverse applications. The use of industrial limestone (ILS) as a filler in polymers can have advantages of changing the properties of pure polymers. Waste eggshells (WE) can be seen as an alternative filler to ILS as they are also a source of calcium carbonate. To assess the feasibility of both filler types and sizes, PLA composites were manufactured by injection molding with filler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…As a result, covalent connections among the fibre and matrix may develop, improving the interfacial bonding of both substances. This helped improve the flexural properties of the hybrid composites [19].…”
Section: Flexural Strengthmentioning
confidence: 99%
“…As a result, covalent connections among the fibre and matrix may develop, improving the interfacial bonding of both substances. This helped improve the flexural properties of the hybrid composites [19].…”
Section: Flexural Strengthmentioning
confidence: 99%
“…After this step, the eggshells are ground to achieve a specific particle size. Second, the eggshell particulates and PLA are mixed in a twin-screw extruder, and pelletized composite material is fed into an injection molding machine [115].…”
Section: ) Cosmeticsmentioning
confidence: 99%
“…Different characteristics of reinforcements/fillers affect PLA composite mechanical properties, such as the reinforcement/filler type, loading concentration, and particle size. In a related study, Betancourt and Cree [5] and Cree and Soleimani [115] investigated the effect of filler type (white eggshells and mineral limestone), loading amounts (5, 10, and 20 wt.%), and particle sizes (63 μm and 32 μm) to produce injection-molded PLA composites. Compared to the pure PLA, the addition of filler loadings of either limestone or eggshells caused tensile strength reductions for both particle sizes, where smaller particles (32 μm) showed a slightly higher tensile strength compared to larger (63 μm) filler particles.…”
Section: Polylactic Acid Composites Reinforced With Eggshell/calcium ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed that the particles were uniformly distributed when less than 4 wt.% fillers were added, while at 5 wt.%, agglomeration occurred. More recently, Cree and Soleimani (2023) [31] investigated the addition of white eggshell powders to PLA. The tensile and flexural strengths peaked when 5 wt.% and 10 wt.% fillers were added, respectively, while the tensile and flexural modulus both improved as the filler loading increased.…”
Section: Introductionmentioning
confidence: 99%